It's not black or white—on the range of vision and echolocation in echolocating bats - Boonman, Arjan; Bar-On, Yinon; Yovel, Yossi (Frontiers in Physiology, 2013)
Around 1000 species of bats in the world use echolocation to navigate, orient and detect insect prey. Many of these bats emerge from their roost at dusk and start foraging when there is still light available. It is however unclear in what way and to which extent navigation, or even prey detection in these bats is aided by vision. Here we compare the echolocation and visual detection ranges of two such species of bats which rely on different foraging strategies (Rhinopoma microphyllum and Pipistrellus kuhlii). We find that echolocation is better than vision for detecting small insects even in intermediate light levels (1-10lux), while vision is advantageous for monitoring far-away landscape elements in both species. We thus hypothesize that, bats constantly integrate information acquired by the two sensory modalities. We suggest that during evolution, echolocation was refined to detect increasingly small targets in conjunction with using vision. To do so, the ability to hear ultrasonic sound is a prerequisite which was readily available in small mammals, but absent in many other animal groups. The ability to exploit ultrasound to detect very small targets, such as insects, has opened up a large nocturnal niche to bats and may have spurred diversification in both echolocation and foraging tactics.